Shocked quartz grains from the Målingen structure, Sweden—Evidence for a twin crater of the Lockne impact structure. (29th May 2014) - Alwmark, C.; Alwmark‐Holm, S.; Ormö, J.; Sturkell, E.
Abstract The Målingen structure in Sweden has for a long time been suspected to be the result of an impact; however, no hard evidence, i.e., shock metamorphic features or traces of the impactor, has so far been presented. Here we show that quartz grains displaying planar deformation features (PDFs) oriented along crystallographic planes typical for shock metamorphism are present in drill core samples from the structure. The shocked material was recovered from basement breccias, below the sediment infill, and the distribution of the orientation of the shock‐produced PDFs indicates that the studied material experienced low shock pressures. Based on our findings, we can exclude that the material is transported from the nearby Lockne impact structure, which means that the Målingen structure is a separate impact structure, the seventh confirmed impact structure in Sweden. Furthermore, sedimentological and biostratigraphic aspects of the deposits that fill the depression at Målingen are very similar to features at the Lockne impact structure. This implies a coeval formation age and thus also the confirmation of the first known marine target doublet impact craters on Earth (i.e., the Lockne–Målingen pair).